Evaluation of the Adequacy of Classroom Facilities and Learning Environment at MTsS Al-Ihsan Pamulang - Munawwaroh, Zahrotul; Azzahra, Nailah; Cerah Lestari, Salsabila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the importance of classroom facilities and learning environments in supporting the comfort and effectiveness of the learning process at MTsS Al-Ihsan Pamulang, focusing on the physical condition of classroom facilities and learning environments, the management of facilities and infrastructure, and their implications for the learning process. This study uses a descriptive qualitative method with a case study design, while data collection techniques are carried out through observation, interviews, and documentation. The results show that the classroom facilities and learning environment at MTsS Al-Ihsan Pamulang are generally adequate to support the learning process, although they do not fully meet the ideal standards. The management of facilities and infrastructure is still contextual and situational, characterized by unstructured planning, unscheduled maintenance, and a simple inventory system. These conditions have implications for the learning process, in which learning can take place functionally, but the comfort of students and the flexibility of teachers in applying learning strategies are not yet optimal. Therefore, it is necessary to strengthen the management of facilities and infrastructure so that the adequacy of classrooms and learning environments can be improved continuously. Keywords : Classroom, Learning Environment, Facilities and Infrastructure